ALOKASI WAKTU KERJA DAN PENDAPATAN PETERNAK SAPI POTONG DI KECAMATAN MEGANG SAKTI KABUPATEN MUSI RAWAS (Working Time Allocation and Income of Cattle Farmers at Megang Sakti Subdistrict Musi Rawas Regency) - Wahyuni, Nenny (Universitas Muhammadiyah Palembang, 2014)
The objectives of this study were to analyze the working time allocation on cattle farmer’s household at Megang Sakti Subdistrict Musi Rawas Regency, to analize the cattle farmer’s income from cattle and the contribution on household income. The method using in this study was survey methods with simple random sampling methods. The objectives were analyzed using data tabulation dan mathematical equation.The results on this study show that the working time allocation on cattle farmer’s household are most used on cattle (42,63%), then for non cattle’s farming (40,67%), and few for non farming activity (16,70%). The highest income on cattle farmer’s household are coming from farming with 69,09 percent contribution, then from cattle’s farming (21,54%) and non farming activity (9,37%).